2006
DOI: 10.1007/s11205-004-6337-7
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Casino Gambling in U.S. Communities

Abstract: This paper empirically analyzes the impact that the spread of casino gambling has on social capital in communities throughout the United States. Social capital is a networking process that translates into an individual's effectiveness in the community and workplace, and binds communities together. Several recent studies have also demonstrated a link between higher levels of social capital and quality of life. In this study, social capital is measured based on six dimensions: trust, civic, volunteerism, group p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…For example, Griswold and Nichols (2006) found that the presence of casino gambling significantly reduces social capital when a casino is located within 15 miles of a community, suggesting that a casino's location influences a community's quality of life and should be considered in the discussions centered on legalized gambling expansion and location within communities. Social capital has been linked to improved quality of life both directly (Griswold & Nichols, 2006) and indirectly, by increasing income or education.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Griswold and Nichols (2006) found that the presence of casino gambling significantly reduces social capital when a casino is located within 15 miles of a community, suggesting that a casino's location influences a community's quality of life and should be considered in the discussions centered on legalized gambling expansion and location within communities. Social capital has been linked to improved quality of life both directly (Griswold & Nichols, 2006) and indirectly, by increasing income or education.…”
Section: Resultsmentioning
confidence: 99%
“…In their article on social capital and health promotion, Hawe and Shiell (2000) surmised that the concepts of power within social environments, building relational ties between members of communities, creating opportunities for empowerment and capacity building by individuals within communities, and working together to create 'healthy' public places and communities, are all the result of effective management of social capital. Sport, as an extension of health promotion activities, create connections between individuals and the networks, norms, and trust that arise from those connections (Griswold and Nichols, 2006;Putnam, 2000). As such, social capital as related to sport builds on three main areas: civic engagement, informal social engagement, and tolerance combined with trust (Griswold and Nichols, 2006).…”
Section: Relationship Of Sense Of Community and Social Capital To Sportmentioning
confidence: 99%
“…Sport, as an extension of health promotion activities, create connections between individuals and the networks, norms, and trust that arise from those connections (Griswold and Nichols, 2006;Putnam, 2000). As such, social capital as related to sport builds on three main areas: civic engagement, informal social engagement, and tolerance combined with trust (Griswold and Nichols, 2006). Civic engagement means working to make a difference in the civic life of communities by developing the combination of knowledge, skills, values and motivation to make a difference.…”
Section: Relationship Of Sense Of Community and Social Capital To Sportmentioning
confidence: 99%
“…It can be argued that recreation, arts, events, and festivals are extensions of health promotion activities, as they create connections between individuals and the networks, norms, and trust that arise from those connections (Griswold & Nichols, 2006;Putnam, 2000). As such, social capital as related to recreation, arts, events, and festivals must build on three main areas: civic engagement, informal social engagement, and tolerance combined with trust (Griswold & Nichols, 2006).…”
Section: Community Studies: a Review Of The Literaturementioning
confidence: 99%
“…As such, social capital as related to recreation, arts, events, and festivals must build on three main areas: civic engagement, informal social engagement, and tolerance combined with trust (Griswold & Nichols, 2006).…”
Section: Community Studies: a Review Of The Literaturementioning
confidence: 99%